REAL STOCK PRICES AND THE LONG-RUN MONEY DEMAND FUNCTION IN MALAYSIA: Evidence from Error Correction Model - Abdullah, Naziruddin; Abd. Majid, M. Shabri (Gadjah Mada International Journal of Business, 2004)
This study adopts the error correction model to empirically investigate the role of real stock prices in the long run-money demand in the Malaysian financial or money market for the period 1977: Q1-1997: Q2. Specifically, an attempt is made to check whether the real narrow money (M1/P) is cointegrated with the selected variables like industrial production index (IPI), one-year T-Bill rates (TB12), and real stock prices (RSP). If a cointegration between the variables, i.e., the dependent and independent variables, is found to be the case, it may imply that there exists a long-run co-movement among these variables in the Malaysian money market. From the empirical results it is found that the cointegration between money demand and real stock prices (RSP) is positive, implying that in the long run there is a positive association between real stock prices (RSP) and demand for real narrow money (M1/P). The policy implication that can be extracted from this study is that an increase in stock prices is likely to necessitate an expansionary monetary policy to prevent nominal income or inflation target from undershooting.